Strong pH-Dependent Near-Infrared Fluorescence in a Microbial Rhodopsin Reconstituted with a Red-Shifting Retinal Analogue - Hontani, Yusaku; Ganapathy, Srividya; Frehan, Sean; Kloz, Miroslav; de Grip, Willem J; Kennis, John T M (The journal of physical chemistry letters, 2018)
Near-infrared (NIR)-driven rhodopsins are of great interest in optogenetics and other optobiotechnological developments such as artificial photosynthesis and deep-tissue voltage imaging. Here we report that the proton pump proteorhodopsin (PR) containing a NIR-active retinal analogue (PR:MMAR) exhibits intense NIR fluorescence at a quantum yield of 3.3%. This is 130 times higher than native PR ( Lenz , M. O. ; Biophys J. 2006 , 91 , 255 - 262 ) and 3-8 times higher than the QuasAr and PROPS voltage sensors ( Kralj , J. ; Science 2011 , 333 , 345 - 348 ; Hochbaum , D. R. ; Nat. Methods 2014 , 11 , 825 - 833 ). The NIR fluorescence strongly depends on the pH in the range of 6-8.5, suggesting potential application of MMAR-binding proteins as ultrasensitive NIR-driven pH and/or voltage sensors. Femtosecond transient absorption spectroscopy showed that upon near-IR excitation, PR:MMAR features an unusually long fluorescence lifetime of 310 ps and the absence of isomerized photoproducts, consistent with the high fluorescence quantum yield. Stimulated Raman analysis indicates that the NIR-absorbing species develops upon protonation of a conserved aspartate, which promotes charge delocalization and bond length leveling due to an additional methylamino group in MMAR, in essence providing a secondary protonated Schiff base. This results in much smaller bond length alteration along the conjugated backbone, thereby conferring significant single-bond character to the C13═C14 bond and structural deformation of the chromophore, which interferes with photoinduced isomerization and extends the lifetime for fluorescence. Hence, our studies allow for a molecular understanding of the relation between absorption/emission wavelength, isomerization, and fluorescence in PR:MMAR. As acidification enhances the resonance state, this explains the strong pH dependence of the NIR emission.
Keywords: fluorescence; rhodopsiny mikrobiální; Protons; protony; Retinaldehyde; Rhodopsins, Microbial; Fluorescence; Schiffovy báze; Schiff Bases; koncentrace vodíkových iontů; retinaldehyd; Hydrogen-Ion Concentration; Spectrum Analysis, Raman; Ramanova spektroskopie